Paying for agricultural productivity - Alston, Julian M.; Pardey, Philip G.; Smith, Vincent H. (International Food Policy Research Institute, 1997)
Throughout the twentieth century improvements in agricultural productivity have been closely linked to investments in agricultural research and development (R&D), but since the 1970s many countries have made major changes in the way they fund and organize public agricultural R&D and in the incentives affecting private R&D. The authors examine these changes in the developed world (highlighting developments in Australia, the Netherlands, New Zealand, the United Kingdom, and the United States) as a step toward evaluating whether the new approaches are raising or lowering the efficiency and effectiveness of R&D.